Sea ice variability : implications for the development of maritime activities around Svalbard - Stocker, Alexandra Nadine, 1991- (2019)
Verkefnið er lokað til 01.06.2020. Climate change is drastically impacting the Arctic environment, leading to rapid sea ice loss. Many commercial sectors perceive the retreating ice edge as an opportunity to expand and develop their industries. Therefore, maritime activities such as shipping, tourism, fisheries, oil and gas exploitation are expected to grow. The overall objective of this thesis is to analyze the relationship between sea ice variability and the development of maritime activities, in particular cruise tourism and fisheries, around Svalbard between 2012 and 2018, while reflecting on the wider governance implications of these transformations. Both cruise tourism and the fishery industry operate close to the ice edge and depend on sea ice services to sail safely in polar regions. To analyse the relationship between sea ice variability and maritime activities, a series of maps were made by using different datasets. The sea ice concentration was derived from passive microwave satellite data retrieved from AMSR-2. The information about vessel mobility was derived from Automatic Identification System (AIS) data provided by the Norwegian Coastal Administration, showing the position of vessels sailing in waters around Svalbard. These datasets were merged, and the analysis reveals a clear increase in maritime activity over the past six years, both in terms of number of vessels operating around Svalbard, and in terms of the stretching of operational seasons. Additionally, decision-makers related to maritime activities in Svalbard were interviewed on the type of information used to consider risk assessment, management and planning in waters with sea ice and how sea ice variability affected decision-making. Combining remote sensing data analysis with interviews with captains, a sea ice researcher, and representatives of fisheries and cruise tourism organisations gave additional insight into how sea ice variability affected maritime activities in the region. The cross-disciplinary approach used in this ...